Inscriptions from Tell Brak 1986 - Illingworth, N.J.J.
Old Akkadian: ТВ 8000, ТВ 8003 - ТВ 8011; Period of the Mitanni Empire: ТВ 8001 (with seal impression of Saustatar, son of Parsatatar, King of Mitanni); ТВ 8002.